2020
DOI: 10.1177/1473325020973265
|View full text |Cite
|
Sign up to set email alerts
|

Making labor visible in the food movement: Outreach to farmworkers in Michigan

Abstract: While the food movement includes many critical positive initiatives, it shows little recognition of the labor contributions of the farmworkers who produce the food. A visit to a few local towns in western Michigan revealed farmworkers are invisible in “farm to table” tropes. A study was undertaken to explore farmworkers and their living conditions, and the links between their local invisibility and historic, political, and global processes. Using ethnographic fieldwork, the author visited housing camps, spoke … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…This study used ethnography and a more extensive methodological description is found elsewhere ( Saldanha, 2020 ). I spent four summers (what farmworkers call growing seasons) shadowing outreach workers.…”
Section: The Study and Its Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This study used ethnography and a more extensive methodological description is found elsewhere ( Saldanha, 2020 ). I spent four summers (what farmworkers call growing seasons) shadowing outreach workers.…”
Section: The Study and Its Methodsmentioning
confidence: 99%
“…This article is not focussed on specific details of findings on outreach such as descriptions of migrant camps and farmworkers living in them, which are published elsewhere ( Saldanha, 2020 ). Instead, it offers a synthesis of best practices of outreach gathered over multiple visits, including the training, preparations, and planning for outreach.…”
Section: The Study and Its Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…19,20 Other studies have also reported that community health workers played critical roles in distributing PPE supplied from government aid packages to farmworkers. 9,21 In addition to a lack of access to PPE, large portions of the Hispanic population in the United States faced food insecurity during the pandemic 22 due to isolation, transportation issues, and economic hardship. Porch drops from the community health workers who participated in our study provided needed food and prescriptions to farmworkers who were isolated in rural housing sites.…”
Section: Discussionmentioning
confidence: 99%
“…Research from several disciplines such as social work (e.g. Saldanha, 2020 ; Zaviršek, 2017 ), public and industrial relations and policy (e.g. Australian Government, 2019 ; Goods et al, 2019 ; Biagi et al, 2018 ; Victorian Government, 2020 ), business and economics (e.g.…”
Section: Gig Work and Migrantsmentioning
confidence: 99%